2011
DOI: 10.2106/jbjs.j.00318
|View full text |Cite
|
Sign up to set email alerts
|

Binge Alcohol Exposure Modulates Rodent Expression of Biomarkers of the Immunoinflammatory Response to Orthopaedic Trauma

Abstract: Our results indicate that acute alcohol intake prior to bilateral femoral fracture with fixation in rats modulates the inflammatory response after injury in a tissue-dependent manner. Although serum biomarkers of inflammation were suppressed in alcohol-treated animals following injury, several measures of pulmonary inflammation including cytokine levels, histological changes, and findings of pulmonary edema were significantly increased following fracture with the presence of alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…Hyper inflammatory responses can be activated by various types of serious injury, that is, hemorrhagic shock, multiple fractures, burns, chest trauma, brain injury, or a combination of injuries [8, 9, 27, 28]; furthermore, changes in cytokine levels are dependent on the degree of injury [29]. It seems that hip fractures, a low energy type of trauma, are insufficient to elicit significant physiologic alterations and immunological reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyper inflammatory responses can be activated by various types of serious injury, that is, hemorrhagic shock, multiple fractures, burns, chest trauma, brain injury, or a combination of injuries [8, 9, 27, 28]; furthermore, changes in cytokine levels are dependent on the degree of injury [29]. It seems that hip fractures, a low energy type of trauma, are insufficient to elicit significant physiologic alterations and immunological reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Current reports indicate that surgery for a hip fracture should be performed as soon as possible to reduce postoperative complications and mortality [1214]. To mimic the injury sustained due to this type of operation, proximal femoral intramedullary pinning was performed immediately following fracture according to Sears et al [9]. Prophylactic preoperative antibiotics (gentamicin, 5 mg/kg) were administered before incision.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgery was performed immediately after fracture according to Sears et al [ 23 ]. Prophylactic preoperative antibiotics (gentamicin, 5 mg/kg) were administered before incision.…”
Section: Methodsmentioning
confidence: 99%
“…Impaired fracture healing related to alcohol exposure is a pathophysiologically relevant alternative for studying fracture repair. Preclinical studies have demonstrated that alcohol exposure impedes fracture callus composition and biomechanical strength[7] and modulates the immunoinflammatory response to blunt orthopaedic trauma[8]. …”
Section: Introductionmentioning
confidence: 99%